Isotherms, Kinetics and Thermodynamic Studies for Removal the Valium from Stomach and Intestine Fluids via Adsorption on Egg Shells Powder (Indian Journal of Forensic Medicine & Toxicology, 2020)
Drug abuse or overdose in accidents is a serious social issue. This study concerned the adsorption behaviourof the Valium drug in both simulated gastric and intestinal pH onto the untreated eggshell powder by usingUV spectroscopy. The effects of various experimental parameters such as contact time, pH-solution, anadsorbent dosage of Valium and temperature range (300-320k) on the adsorption capacities have beeninvestigated. The suitability of Langmuir and Freundlich adsorption models to the experimental equilibriumdata at different solution temperatures were calculated. The adsorption was well described by the Freundlichisotherm model and Langmuir, S3 for the stomach and S2 for the intestine according to the Giles classification.Thermodynamic parameters such as ?H°, ?G°, and ?S° results showed that the adsorption of the drugincreases by increasing the temperature in the stomach solution, i.e., the endothermic reaction decreases byincreasing the temperature at the intestinal solution, i.e., the reaction is exothermic. Experimental data werealso tested in terms of adsorption kinetics, the results illustrated that the adsorption process was followingpseudo-second-order kinetics in the stomach solution and first order in the intestinal solution.